THE CHARACTERISTIC OF THE CORPORATE CONFLICT ASSITUATIONS OF THE IMPERFECTSPECIFICATION OF THE PROPERTYRIGHTS - Marina E. Sklyarova (Статистика и экономика, 2016)
In paper conditions of the perfect and imperfect specification of the property rights are analyzed. The conflict as a situation of the imperfect specification of the property rights is considered, the concept of the conflict from the point of view of the specification of the property rights and conditions of its occurrence is given.The estimation of interrelation of negative dynamics of economic parameters of the organization and presence of a disputed situation on the basis of the analysis and calculation of statistical data is resulted.